The Protective Effects of Zornia diphylla (L.) Pers. Against Acute Liver Injury Induced by Carbon Tetrachloride in Mice - Xie, Su-Zhi; Zhai, Xiang-Yang; Xi, Sheng-Yan; Qiu, Ying-Kun; Zhang, Yu-Mei; Kong, Xiang-Jun; Li, Yun-Hong; Zhu, Lin; Wang, Zheng; Zhang, Shan-Gang; Huang, Shu-Qiong; Lu, Da-Wei; et al. (Frontiers in Pharmacology, 2021)
Background: Zornia diphylla (L.) Pers. (ZDP) is a traditional Chinese herbal medicine that has been used for several decades to treat patients with liver diseases. Whether ZDP is best administered as a single agent or adjunctive therapy has yet to be determined as does the mechanism whereby it exerts its effects on antagonizing acute liver injury (ALI). Aim of the study: To investigate the protective effects of ZDP on ALI induced by carbon tetrachloride (CCl4) and the potential underlying mechanisms. Materials and Methods: Sixty adult mice were randomized into six study groups (n = 10/group). Three groups were treated with different concentrations of ZDP (2.5, 1.25, 0.625 g/kg), one with bifendate (0.0075 g/kg) alone (positive control) and one with physiologic saline (normal, negative control). All groups were treated for 14 days. Two hours after the last administration, the normal group received an intraperitoneal injection of peanut oil, and the other five groups received an intraperitoneal injection of an equal dose of CCl4 peanut oil solution. At 24 h, the liver index, histology and serum or tissue levels and/or protein expression of AST, ALT, TBIL, ALP, SOD, MDA, CAT, GSH, Akt, p-Akt, NF-κB p65, IκB-α, IL-1β, IL-6, TNF-α, E-cadherin and vimentin were determined. Results: Compared to the model controls, the degree of inflammatory cell infiltration and hepatocyte injury of liver tissue was relieved in the bifendate and three ZDP groups; liver index in the ZDP (2.5, 1.25 g/kg) groups and serum liver function indices in the ZDP (2.5, 1.25 and 0.625 g/kg) groups were decreased; antioxidants SOD, CAT and GSH in liver tissue were increased but the lipid peroxidation index MDA was decreased; protein expression of inflammatory cytokines Akt, p-Akt, NF-κB p65, IκB-α, IL-1β, IL-6 and TNF-α in the liver was ameliorated, and E-cadherin expression was increased. The results of liver histopathology also showed that ZDP had a significant effect on ALI. Conclusions: ZDP has obvious protective effects on CCl4-induced ALI as a single therapy and appears to act by inhibiting oxidation, reducing the release of inflammatory factors and promoting hepatocyte repair.